Development of a learning content management system based on interactive learning object approach - Yavuz Akpinar; Huseyin Simsek (2005 6th International Conference on Information Technology Based Higher Education and Training : [proceedings] : July 7-9, 2005, Santo Domingo, Dominican Republic, 2005)
Learning difficulties have been neglected due to over-focusing on technology and dissemination of content. Many of such endeavors targeted on delivering content packages to students and/or trainees; once the content was delivered, all responsibility of learning was loaded to the learners. The only support to them was through e-communication facilities which were also treated as a revolutionary mean to student-student and student-instructor communication. Such communication is treated as sufficient for facilitating learning. The learning content organization tools supporting certain content packaging and delivery standards were short of facilities to support activity-based learning content. This study outlines a set of guidelines to develop a learning content management system which would serve content development on line, making it a time and place independent process. The guidelines are based on more interactivity in learning objects, recording students' reactions to learning materials, cooperation of teachers, enabling a reusable learning object to accomplish a set of instructional objectives, contextualization of content in learning object is encouraged, metadata focusing more on cognitive involvement and functionalities of the learning setting.